Dampak Faktor Perilaku terhadap Praktik Akuntansi Modern - Amril Amril; Helmy Syamsuri (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the role of professionalism and ethics in controlling the complexity of modern accounting practices at financial sector State-owned enterprises in Makassar City. The complexity includes the use of information system-based accounting technology, integration of financial data across units, and increasing pressure on transparency and accountability of financial reporting. The approach used was qualitative with descriptive methods, and data were obtained through in-depth interviews, observation, and documentation. Research informants consist of internal accountants, auditors, and financial managers who are directly involved in the implementation of modern accounting systems. The results showed that professionalism plays an important role in encouraging adaptive attitudes, responsibility, and commitment to improving individual competence in the face of technological change. Meanwhile, ethics proved to be a moral foundation in making fair and independent decisions, especially when facing pressure or potential irregularities in reporting. Professionalism and ethics synergistically function as behavioral controllers capable of maintaining the integrity and quality of financial information. This research confirms the importance of internalizing ethical values and strengthening professional culture as part of the organization's strategy in managing modern accounting challenges in a sustainable manner.